CONGENITAL INTRAORAL DERMOID CYST WITH CERVICAL EXTENSION MANAGED VIA A SINGLE INTRAORAL APPROACH IN A NEONATE: A CASE REPORT (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Dermoid cysts of the oral cavity are rare congenital lesions arising from ectodermal tissue entrapment during embryogenesis. In neonates, these lesions are uncommon but clinically significant due to their potential to cause feeding difficulties and airway compromise depending on their size and anatomical location. Case Presentation: We report a case of a male neonate presenting with swelling involving the oral cavity and left side of the neck since birth. The infant had difficulty swallowing and was dependent on bottle feeding. The patient re-presented at two months of age with fever and progressive increase in swelling size. Clinical examination revealed a tense, fluctuant, non-tender cystic swelling involving the sublingual region and left submandibular area. Magnetic Resonance Imaging demonstrated two well-defined ovoid cystic lesions. The intraoral lesion measured approximately 3.5 × 2.5 × 1.5 cm, and the cervical component was located adjacent to the submandibular gland. Fine Needle Aspiration Cytology (FNAC) revealed benign squamous cells with inflammatory background and yielded characteristic milky white fluid, suggestive of a dermoid cyst. This case is unique due to the presence of both intraoral and cervical components, which were successfully managed through a single intraoral approach, thereby avoiding the need for an external incision. Therapeutic Intervention and Outcome: The patient underwent complete surgical excision via an intraoral approach under general anesthesia. The cervical component was mobilized, decompressed, and delivered intraorally, enabling total excision without an external incision. Postoperative recovery was uneventful except for transient edema, which resolved within a few days. Histopathological examination confirmed the diagnosis, and no recurrence was observed on follow-up. Conclusion: Early diagnosis and complete surgical excision are essential for successful management. The intraoral approach provides excellent functional and cosmetic outcomes, even in lesions with cervical extension, while preventing complications such as infection and airway compromise.